The Use of Damdaman Educational Play Tools to Develop Logical Thinking Skills in Children at TK Islam Bakti 63 Tanjung Harapan - Setianingsih, Erdilla Ani; Sunimaryanti, Sunimaryanti; Andre, Lesis; Siska , Widia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The research problem focuses on the use of the educational game tool damdaman to enhance children's logical thinking skills, which were previously at the